PENGARUH BLENDED LEARNING TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS dan SELF EFFICACY SISWA - Nurzain Khilmi R (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
The purpose of this study was to know the effect of Blended Learning on the ability of Mathematical Representattion and Self efficacy. Populations of this study were all students of class VIII in one of SMP in Purwokerto at 2018. It was experimental study post test only disgn. The sampel were students of class VIII G as the experimental class and class VIII D as the control class. The average of post test result of the students’ mathematical representation ability reach 70,30 for the experimental class and 62,08 for the control class. After a hypothesis testing by using Man Whitney test was obtained significance value of 0,036. Due to the significance value was smaller, so H0 was rejected. It can be concluded that the mathematical representation of students using blended learning was higher than students using direct learning or the blended learning has an effect on mathematical representation.The average of questionnaireof result of the students’ efficacy ability reach 77,05 for the experimental class and 74,91 for the control class. After a hypothesis testing by using Man Whitney test was obtained significance value of 0,254. Due to the significance value was bigger, so H0 was accepted. It can be concluded that there was no difference between the students’ self efficacy by blended learning and direct learning or the blended learning has no effect on student’ efficacy.